Quantifications of Lipid Kinetics In Vivo Using Stable Isotope Tracer Methodology - Il-Young Kim; Sanghee Park; Jiwoong Jang; Robert R. Wolfe (The Korean Society of Lipid and Atherosclerosis, 2020)
Like other bodily materials, lipids such as plasma triacylglycerol, cholesterols, and free fatty acids are in a dynamic state of constant turnover (i.e., synthesis, breakdown, oxidation, and/or conversion to other compounds) as essential processes for achieving dynamic homeostasis in the body. However, dysregulation of lipid turnover can lead to clinical conditions such as obesity, fatty liver disease, and dyslipidemia. Assessment of "snap-shot" information on lipid metabolism (e.g., tissue contents of lipids, abundance of mRNA and protein and/or signaling molecules) are often used in clinical and research settings, and can help to understand one's health and disease status. However, such "snapshots" do not provide critical information on dynamic nature of lipid metabolism, and therefore may miss "true" origin of the dysregulation implicated in related diseases. In this regard, stable isotope tracer methodology can provide the in vivo kinetic information of lipid metabolism. Combining with "static" information, knowledge of lipid kinetics can enable the acquisition of in depth understanding of lipid metabolism in relation to various health and disease status. This in turn facilitates the development of effective therapeutic approaches (e.g., exercise, nutrition, and/or drugs). In this review we will discuss 1) the importance of obtaining kinetic information for a better understanding of lipid metabolism, 2) basic principles of stable isotope tracer methodologies that enable exploration of "lipid kinetics" in vivo, and 3) quantification of some aspects of lipid kinetics in vivo with numerical examples.